PENGARUH KEMUDAHAN PENGGUNAAN, KUALITAS PELAYANAN,HARGA DAN PROMOSI TEHADAP KEPUASAAN PELANGGAN GRABFOOD - Satria Abdi Pratama Yudha; Rois Arifin; M. Hufron (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACTThis study aims to discuss the effect of ease of use, service quality, price and promotion of grabfood customer satisfaction in communities in the lowokwaru sub-district of Malang. using non-probability techniques with purposive sampling sampling techniques with special criteria. of the total population of 194,521 inhabitants of the lowokwaru sub-district of Malang city, 100 respondents were eligible. Data analysis in this study using SPSS 17. Application data used in this study include multiple linear regression analysis, validity test, reliability test, normality test, classic assumption test and hypothesis test. From the results of multiple linear regression analysis, it is known that simultaneous ease of use, service quality, price and promotion variables influence customer satisfaction. While the results of the t-test analysis revealed that the ease of use, servant quality, price and promotion variables had a significant influence on customer satisfaction.Keywords: Ease of Use; Service Quality; Price; Promotion; Customer Satisfaction